Classroom-based L2 vocabulary learning and comprehension: Replications of Lesaux, Kieffer, Faller & Kelley (2010). (10th August 2016) - Durgunoğlu, Aydin Yücesan; Bigelow, Martha
Abstract : The field of language teaching and learning is in dire need of replications of vocabulary and comprehension research with diverse populations of learners. We propose for replication one large-scale vocabulary intervention carried out successfully in a middle-school with monolingual and multilingual students. This study was carried out several years ago, was published in the Reading Research Quarterly, and has been generously cited since then. The findings and the instruments from this study have been leveraged in subsequent extension studies by the same group of researchers, but have not been replicated in different contexts. We offer multiple reasons and methods of replicating this study in high school and adult contexts in which there is a serious need for learners to comprehend technical or academic materials using deep, nuanced foundations of vocabulary.